2013
DOI: 10.1002/chem.201203405
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Solvent Effect on the Hydrostannylation of Propargylic Alcohol Derivatives with nBu3SnH/Et3B at Room Temperature

Abstract: The solvent is key: A general protocol is described for the hydrostannylation of propargyl alcohol derivatives at room temperature using Et3B/O2 as the promoter (see scheme). Rate and mechanistic studies point to a different autoxidation product of Et3B in THF than is observed in benzene, the typical solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 87 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…As well as providing many sophisticated examples of stereodefined trisubstituted olefin synthesis via this approach, , we subsequently went on to employ it for a new and fully stereocontrolled formal total synthesis of the frog alkaloid, (+)-pumiliotoxin B, by a route which greatly improved and shortened the original pathway to this molecule. Our (+)-pumiliotoxin B paper also presented our expanded thoughts on the highly complex mechanism of this novel hydrostannation reaction, which is not a simple process by any means, but one that operates through a complex radical mechanism in which there are multiple competing Ph 3 Sn radical addition/elimination and vinylstannane isomerization events all occurring concurrently and cooperatively, with the result that α-tri­phenyl­stan­nylated alkenes of general structure 2 eventually predominate over time.…”
mentioning
confidence: 99%
“…As well as providing many sophisticated examples of stereodefined trisubstituted olefin synthesis via this approach, , we subsequently went on to employ it for a new and fully stereocontrolled formal total synthesis of the frog alkaloid, (+)-pumiliotoxin B, by a route which greatly improved and shortened the original pathway to this molecule. Our (+)-pumiliotoxin B paper also presented our expanded thoughts on the highly complex mechanism of this novel hydrostannation reaction, which is not a simple process by any means, but one that operates through a complex radical mechanism in which there are multiple competing Ph 3 Sn radical addition/elimination and vinylstannane isomerization events all occurring concurrently and cooperatively, with the result that α-tri­phenyl­stan­nylated alkenes of general structure 2 eventually predominate over time.…”
mentioning
confidence: 99%
“…Specifically, we have summarised the firm experimental evidence that we have gathered which supports the position that the Ph 3 SnH hydrostannation reactions are genuinely O‐directed and totally free radical in their nature, and all suggestions,,,, including implicit ones that the regiochemistry of these processes is primarily dictated by alkyne ground state polarity have been refuted, at least for the propargylically‐oxygenated alkyl acetylene systems. We have also rationalised the free radical hydrostannation outcomes of Organ and Kobayashi's 1‐alkyl‐3‐trifluoromethyl propargyl alcohol systems and explained their results via a fully free radical mechanism that involves dual reagent O‐coordination and electronic control, with both effects cooperating strongly in this specialised type of alkyne system.…”
Section: Summary and Final Thoughtsmentioning
confidence: 86%
“…In other words, acetone, with its much higher dielectric constant, is much more polar than is THF, and it should therefore potentially be a much better solvent at stabilising a charged ion pair (if one was being formed). The use of acetone as the reaction solvent should, according to the Scheme team's mechanistic analysis,, have markedly increased the rate of hydrostannation of 382 with Bu 3 SnH/Et 3 B, if their 2013 mechanism held true, and their polar solvent rate acceleration effect was genuinely significant and “pronounced”, as they have stated in the title of reference [38].…”
Section: Our 2005 Experimental Investigations Into the Mechanism Of Tmentioning
confidence: 99%
“…A combination of control experiments, including the polar solvent studies, deuterium-labeling studies, and DFT calculations provide crucial insights into the mechanistic details of the hydrostannation. Because the addition of Bu 3 Sn–H to a wide selection of alkynes proceeds only in the presence of O 2 , and is faster in polar solvents, it has been concluded that the reaction does not proceed exclusively by a radical process. Instead, it is suggested to involve the formation of cationic species 27 through O 2 -promoted single-electron transfer (SET) oxidation of alkenyl radicals 26 (Scheme ).…”
Section: Mechanism and Stereochemistrymentioning
confidence: 99%